Emotion regulation and angry mood among adolescents with externalizing problems and intellectual disabilities. (February 2021) - te Brinke, Lysanne W.; Schuiringa, Hilde D.; Matthys, Walter
Highlights: Adolescents with intellectual disabilities are at risk for externalizing problems. They report fewer regulation difficulties than adolescents without disabilities. They rely more on behavioral rather than cognitive regulation strategies. This is a starting point to understand emotion regulation of at risk adolescents. Implications for interventions and future research are discussed. Abstract: Background and aims: Cognitive behavior therapy targeting emotion regulation is found to be effective in decreasing externalizing problems, but little is known about the emotion regulation capacities of adolescents with externalizing problems and Mild Intellectual Disabilities or Borderline Intellectual Functioning (MID-BIF). Therefore, the aim of this study was to compare emotion (i.e., anger) regulation capacities, angry mood level and angry mood variability between two groups: adolescents with externalizing problems and MID-BIF and adolescents with externalizing problems and average intelligence (AIQ). Methods and procedures: Participants in the MID-BIF ( n = 42, M age = 15.52, SD = 1.43) and AIQ ( n = 39, M age = 13.67, SD = 1.06) group completed questionnaires about emotion regulation difficulties, emotion regulation strategies, and angry mood. Outcomes and results: Adolescents in the MID-BIF group reported fewer emotion regulation difficulties, fewer maladaptive regulation strategies, and lower levels of angry mood than adolescents in the AIQ group. No between-group differences in angry mood variability were found. Lastly, adolescents in the MID-BIF group reported to use more behavioral than cognitive regulation strategies. Conclusions and implications: These findings provide a starting point in understanding emotion regulation and angry mood of adolescents with externalizing problems and MID-BIF and show that it is important to consider differences between cognitive and behavioral regulation processes.